2022
DOI: 10.1111/arcm.12815
|View full text |Cite
|
Sign up to set email alerts
|

New data on relevant ancient Egyptian wooden artifacts: Identification of wooden species and study of the state of conservation with multidisciplinary analyses

Abstract: Wood species identification and characterization of its weathering processes are crucial steps in the scientific approach of conservation of wooden cultural heritage. Many precious wooden objects of ancient Egypt are largely present in museums, nevertheless relatively little information is available concerning the nature of timber used and on their status of conservation. To address this gap, the wooden species of three relevant archaeological wood objects (statue, box, and coffin) arising from different Egypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…using SEM. Major alterations in the chemical configuration of the wood due to microbial corrosion and a reduction in the crystallinity index of cellulose were also found by Geweely et al [31].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…using SEM. Major alterations in the chemical configuration of the wood due to microbial corrosion and a reduction in the crystallinity index of cellulose were also found by Geweely et al [31].…”
Section: Discussionsupporting
confidence: 52%
“…The experimental aged wooden cubes treated with the most efficient thyme essential oil were analyzed using a scanning electron microscope, energy dispersive X-ray analysis (SEM & EDX), and Fourier-transform infrared spectroscopy (FTIR). The observed drop in the crystallinity index in the untreated wood may be due to fungal deterioration, as recorded by Geweely et al [31] who stated that the XRD analysis of the archaeological materials revealed a drop in their crystalline index, which was caused by microbial degradation. Moreover, Sparacello et al [91] evaluated the potential changes to the wooden artwork surfaces pre-and post-treatment with Thymus vulgaris and a hydro-alcoholic solution using SEM, EDX, and FTIR.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A unique comparison of chemical, natural essential oil, and physical (ozone) for preservation of archaeological items against microbial deterioration was documented by Geweely et al (2022) . Chemical preservation of historical artifacts poses a risk to both the environment and human health, as well as degradation (erosion and surface damage).…”
Section: Conservation Of Inorganic Deteriorated Archaeological Objectsmentioning
confidence: 99%
“…Microbial degradation was then conducted on the PLM carriers using the isolated microorganisms. The hierarchical structures of the PLM carriers after microbial degradation were characterized using various technical methods [16,17], such as scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), attenuated total reflectance-Fourier transform infrared spectrometry (ATR-FTIR), and X-ray diffraction (XRD). Additionally, nanoindentation (NI) technology was applied to the PLM carriers for the first time to explore the response mechanism of leaf fiber micromechanics under the microbial degradation.…”
mentioning
confidence: 99%